MINERALOGY AND SEDIMENT DISTRIBUTION BASED ON GRAIN SIZE ANALYSIS IN THE KAPUAS AREA, CENTRAL KALIMANTAN - Diwantara, Raja Hertansyah; Rosana, Mega Fatimah; Ernowo, Ernowo; Sunarie, Cecep Yandri (Journal of Geological Sciences and Applied Geology, 2025)
The Kapuas region in Central Kalimantan exhibits intriguing geological potential due to the presence of a large river and sediment flows closely associated with fluvial activity. This study aims to identify the distribution of sediment grain sizes and the presence of heavy minerals in the study area. Sediment sampling locations were identified at four points using shallow drilling techniques, specifically with a hand auger. The research methods employed include grain size analysis (granulometry) and grain counting analysis using polarized microscopy. The results indicate that the grain sizes in the study area range from coarse to fine sand. The sediment transport mechanism occurs as bedload for coarse-sized sediments and in suspension for fine-sized sediments. The mineralogical composition of sediments in the study area contains heavy minerals such as rutile, ilmenite, cassiterite, biotite, hematite, zircon, and chalcopyrite. The varied mineral content reflects a source material origin from acidic to intermediate igneous rocks and metamorphic rocks. This indicates a complex and dynamic geological history in the region.